2014
DOI: 10.17265/2161-6264/2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Yield and Quality in Some Banana Varieties Applied with Commercially Manufactured Biostimulant Aquasap from Sea Plant Kappaphycus alvarezii

Abstract: A field study was conducted to investigate the effect of Aquasap, a commercially manufactured biostimulant from seaweed Kappapphycus alvarezii on some hills and foothills banana varieties namely Robusta (AAA), Njali poovan (AB), Red banana (AAA) and Nendran (AAB) by applying at 5% through foliar spray at the 3rd, 5th and 7th month of plantation. Both quantitative and quality data of fruits were analyzed along with vegetative growth of the plants. The seaweed biostimulant was found very effective on increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The extract used at 1% concentration in culture peanut (Arachis hypogea L.) resulted in an increased yield of 30.6% %. Karthikeyan and Shanmugam (2014) observed that banana varieties of hills and foothills viz. Robusta (AAA), Njali poovan (AB), Red banana (AAA), and Nendran (AAB) had responded well to biostimulant of seaweed K. alvarezii to 5% with average yields increase of 56.58%, 19.08%, 39.35%, and 11.46%, respectively.…”
Section: Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract used at 1% concentration in culture peanut (Arachis hypogea L.) resulted in an increased yield of 30.6% %. Karthikeyan and Shanmugam (2014) observed that banana varieties of hills and foothills viz. Robusta (AAA), Njali poovan (AB), Red banana (AAA), and Nendran (AAB) had responded well to biostimulant of seaweed K. alvarezii to 5% with average yields increase of 56.58%, 19.08%, 39.35%, and 11.46%, respectively.…”
Section: Itemsmentioning
confidence: 99%
“…The extract can be used as a biofertilizer or agricultural stimulant, when applied as foliar "spray" and its efficiency has been reported by many authors (Karthikeyan and Shanmugam, 2014;Mondal et al, 2015;Karthikeyan and Shanmugam, 2017;Layek et al, 2018;Vasantharaja et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Application of 3-4 foliar applications based on the crop cycle improved the growth, yield, and quality of the produce. An increase of 11% to 52% in the yield levels were noticed for different vegetable crops" Karthikeyan and Shanmugam [9]. Keeping in view the above fact, the experiment was conducted to find out "Influence of Seaweed Sap and Zinc on growth and yield of Baby corn (Zea mays L.)"…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves are considered as one of the most important floras in the world that can easily adapt to extreme environmental conditions (Long & Giri, 2011) [72] . Across more than 100 countries, mangrove ecosystem has been threatened of rapid loss of destruction contributing immense ecological and economical damages (IPBES, 2019;Gevaña et al, 2019;Duke et al, 2007) [25,23,16] . In the Philippines, many studies had been reported that 50% of mangrove forest loss as of the year 2000 (Cervantes, 2021; Garcia et al, 2014;Long & Giri, 2011;Spalding et al, 2010;Yparraguire, 2008;Primavera et al, 2004) [10,22,72,62,71,50] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies on nutrient addition of mangroves used systemic application of biostimulant than foliar application elaborating the function of the root system in the distribution of nutrients to the stem and leaves of plants (Mangora, 2016;Chen & Ye, 2014;Lovelock et al, 2009;Martin, 2007;Lovelock et al, 2004;Parida & Das, 2004;Feller et al, 2002;Feller et al, 1999;Naidoo, 1987) [33,72,28,33,30,42,19,21,36] . On the other hand, seaweed (K. alvarezii) extract has been reported that promotes plant growth in various crops but limited on marine plants like mangroves ( [5,25,46,13,63] . From these points, it could be hypothesized that the seaweed extract of K. Alvarezii as biostimulant can significantly increase the growth of mangrove propagules through foliar application.…”
Section: Introductionmentioning
confidence: 99%